Area Under the Curve dan Akurasi Cystatin C untuk Diagnosis Acute Kidney Injury pada Pasien Politrauma - Maskoen, Tinni T.; Purnama, Djaya (Majalah Kedokteran Bandung, 2018)
Pasien yang mengalami cedera dengan Injury Severity Score (ISS) >16 didefinisikan sebagai politrauma. Pada politrauma terjadi hipoksia jaringan, autoregulasi terganggu, mikrosirkulasi glomerulus, cedera sel tubular serta proses inflamasi yang apabila tidak diatasi secara adekuat dapat menyebabkan acute kidney injury (AKI). Saat ini diagnosis AKI berdasar atas kenaikan kreatinin serum yang terdeteksi setelah terjadi kerusakan ginjal. Cystatin C merupakan penanda biologis yang dapat mendeteksi AKI. Tujuan penelitian ini adalah mengetahui nilai area under the curve (AUC) dan akurasi cystatin C untuk diagnosis AKI pada pasien politrauma di Instalasi Gawat Darurat (IGD) RSUP Dr. Hasan Sadikin Bandung. Penelitian uji diagnostik ini dengan analisis data sekunder pada sebagian data penelitian Academic Leadership Grant (ALG) pasien politrauma di IGD RSUP Dr. Hasan Sadikin Bandung dari Januari–Juni 2017. Analisis data menggunakan kurva receiver operating characteristic (ROC) dengan program statistical product and service solution (SPSS)versi 24.0 for windows. Hasil penelitian dari 23 sampel menunjukkan pada cut-off point 354,97 ng/mL cystatin C plasma memiliki sensitivitas 100%, spesifisitas 88,9%, nilai duga positif 71,4%; nilai duga negatif 100%; nilai AUC 0,967; dan akurasi 91,3%. Simpulan penelitian ini adalah nilai AUC dan akurasi cystatin C memberikan hasil yang baik dalam diagnosis AKI pada pasien politrauma. Kata kunci: Acute kidney injury, akurasi, cystatin C, nilai AUC, politrauma Area Under the Curve and Cystatin C Accuracy for Acute Kidney Injury Diagnosis in Polytrauma Patients Patients experiencing injuries with an Injury Severity Score (ISS) of >16 are defined as polytrauma patients. Polytrauma can cause hypoxia, disruption of autoregulation, glomerular microcirculation, tubular cell injury, and inflammation processes that, without adequate treatment, may lead to acute kidney injury (AKI). The current diagnosis of AKI is based on the elevated serum creatinine that can be detected after kidney damage. Cystatin C is a biomarker that can detect AKI. The aim of this study was to determine the value of area under the curve (AUC) and accuracy of cystatin C for diagnosing AKI in polytrauma patients in the Emergency Room (ER) of Dr. Hasan Sadikin Bandung. A diagnostic test study using secondary data from theAcademic Leadership Grant (ALG) study onpolytrauma patients in the ER of Dr. Hasan Sadikin General Hospital Bandung, from January 2017âˆ’June 2017 was performed. Data was analyzed using the receiver operating characteristic (ROC) curve with statistical product and service solution (SPSS) version 24.0 for windows. Results from 23 samples showed that the cut off point of plasma cystatin C was 354.97ng/mL with a sensitivity of 100.0%, specificity of 88.9%, positive predictive value of 71.4%, negative value of 100.0%, AUC value of 0.967 and accuracy of 91.3%. Hence, the AUC values and cystatin C accuracy present good results for diagnosing AKI in polytrauma patients. Key words: Accuracy, acute kidney injury, cystatin C, the value of AUC, polytrauma